A função [Phi] de Euler e a expansão periódica de frações na base b - Rech, Marcionei (2015)
This study aims to explore the behavior of the expansion of common fractions, the length of the non-periodic part and the period if it is an infinite tithe, with the aid of ϕ Euler function. Besides the decimal expansions, which are the most common, we will explore the expansions using any base b, or another numbering system, in order to generalize some results that are easily observed in the decimal number system. We shall resume some concepts: number systems, prime numbers, the function ϕ of Euler and Euler’s Theorem, which are important to base our discussions. We will show some examples of expansion of common fractions for different numerical bases resulting in finite decimals, and simple and composite periodic decimals.